The Influence of School Culture on Students' Learning Motivation at Sman 2 Mataram - Junaidin, Junaidin; Akbar, Muhammad Ali; Shahab, Putri Hindun Anifayakun (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to examine the influence of school culture on student learning motivation at SMAN 2 Mataram. School culture, which encompasses the values, norms, and practices developed within the school environment, plays a significant role in shaping student motivation. The research employs a mixed-method approach, consisting of descriptive observation and literature review, to understand the dynamics of school culture and its impact on student motivation. The findings indicate that a positive school culture, such as discipline, hard work, and strong teacher-student relationships, can enhance student learning motivation. Student involvement in extracurricular activities also contributes to their increased motivation. However, challenges such as motivation gaps between students and limited resources need to be addressed to build an ideal school culture. The study suggests the importance of strong leadership, parental involvement, and adequate facilities to foster a positive school culture and improve student learning motivation